Impact of Maternal Folic Acid Supplementation on Descendants' Kidney in Adulthood - Fernandes, Thayane Ferreira da Costa; Conde, Poliana dos Santos; Brasil, Flavia de Bittencourt; Oliveira, Marcos Roberto de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Supplementation with folic acid (FA) during gestation has been recommended by medical society all over the world, but some studies have shown that intake of high folic acid diet may unleash damages to the descendants. Objectives: Describing the effects of maternal supplementation with FA during gestation on offspring's kidney at late life stages. Data Source: It is a systematic review by which were consulted the following databases: Medline, through Pubmed, Lilacs, and SciELO. The research was performed using the keywords “Folic acid”, “Gestation” and “Kidney”. Study Selection: Eight studies were regarded for this systematic review. Data Collection: Only studies that evaluated folic acid consumption during gestation and its effects exclusively on descendants' kidney at several phases of life were regarded. Results: Gestational FA intake did not change the renal volume, glomerular filtration rate and the expression of some essential genes in the kidney of puppies whose dams were supplemented with FA. Maternal consumption of double FA plus selenium diet was effective in preserving antioxidant enzymes activity in the kidney of descendants from mothers exposed to alcohol. FA supplementation decreased some gross anomalies in the puppies caused by teratogenic drug despite of had not been effective in preventing some renal architectural damages. Conclusion: FA supplementation did not cause renal toxicity; it exerted an antioxidant protective effect and mitigated some renal disorders caused by severe aggressions.
Keywords: Folic acid; Gestation; Kidney; Descendant; Adulthood